2017
DOI: 10.1093/gbe/evx082
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Evidence that Methanotrophic Endosymbionts Likely Provide Deep-Sea Bathymodiolus Mussels with a Sterol Intermediate in Cholesterol Biosynthesis

Abstract: Sterols are key cyclic triterpenoid lipid components of eukaryotic cellular membranes, which are synthesized through complex multi-enzyme pathways. Similar to most animals, Bathymodiolus mussels, which inhabit deep-sea chemosynthetic ecosystems and harbor methanotrophic and/or thiotrophic bacterial endosymbionts, possess cholesterol as their main sterol. Based on the stable carbon isotope analyses, it has been suggested that host Bathymodiolus mussels synthesize cholesterol using a sterol intermediate derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 44 publications
2
55
0
Order By: Relevance
“…RNA probes for FISH were prepared as described previously [47,48]. To synthesize RNA probes, amplifications of 16S rRNA, hydABs, and soxB genes were conducted by PCR using primers, which were designed based on the sequence data from Tables S2 to S3 and using the constructed plasmids as templates; then the amplicons were ligated into a pTA2 vector (Toyobo, Osaka Japan).…”
Section: Fish Analyses Of 16s Rrna and Transcripts Of Hydab And Soxbmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA probes for FISH were prepared as described previously [47,48]. To synthesize RNA probes, amplifications of 16S rRNA, hydABs, and soxB genes were conducted by PCR using primers, which were designed based on the sequence data from Tables S2 to S3 and using the constructed plasmids as templates; then the amplicons were ligated into a pTA2 vector (Toyobo, Osaka Japan).…”
Section: Fish Analyses Of 16s Rrna and Transcripts Of Hydab And Soxbmentioning
confidence: 99%
“…In situ hybridization was carried out as described previously [47,48], with the following modifications. The gill tissues excised from the in situ fixed individuals were refixed in Davidson's solution (10% glycerol, 40% formaldehyde, 30% ethanol, and 30% filtered artificial seawater) at −30°C for 24 h and at 4°C for 16 h, followed by stepwise dehydration in an ethanol series.…”
Section: Fish Analyses Of 16s Rrna and Transcripts Of Hydab And Soxbmentioning
confidence: 99%
“…Symbiotic MOBs were puri ed using a method reported previously with some modi cations [33]. In short, gill tissue was homogenized on ice and ltered using sterilized gauze and nylon lters, with successive pore sizes of 10, 5, and 3 µm.…”
Section: Methodsmentioning
confidence: 99%
“…However, the mechanisms controlling the symbiosis between G. platifrons and symbiotic MOBs still remain largely unknown due to the unavailability of cultivable symbionts and accessible mussels. Several methods have been used to harvest symbionts from Bathymodiolinae mussels to date, including enrichment by differential centrifugation and density gradient centrifugation [33][34][35][36]. It has been found that far fewer MOBs can be yielded from density gradient centrifugation compared to differential centrifugation, although their purity is better.…”
Section: Global Immune Response Of Gigantidas Against Mobs and Nonsymmentioning
confidence: 99%
“…Nutrient interdependence strengthens the interactions between host and symbionts, leading to strong and stable symbiosis (105,106). Transporters for carbohydrates, lipids, and amino acids were all available in symbionts' genomes, and they even expanded in some symbionts.…”
Section: Downloaded Frommentioning
confidence: 99%